We called them giants - Gillen, Kieron (Image Comics, 2024)
"Lori wakes to find the streets empty. Everyone has gone. Or at least, nearly everyone. She's thrown into a world where she has to scrape by in the ruins of civilization, nearly starving, hiding from gangs when They arrive."--